Building Ontology-Based Annotations for Personal Information Management Systems – The SemanticLIFE Design and Implementation Case - Mustofa, Khabib; Tjoa, A Min (2006)
Since the introduction of the semantic Web idea, many tools have been developed to harvest the advantage of machine-understandable data. Ontology and metadata are the two basic enabling requirements therefore. SemanticLIFE is a personal information management system which deals with data and metadata originating from various sources. Being developed on the basis of semantic Web technology standards, the system involves ontologies and represents metadata in RDF(S) or OWL. To enrich metadata for the system, semantic annotation is considered essential and hence this paper discusses the annotation approach implemented for SemanticLIFE. Due to the variety of data sources, annotation is not solely addressed to Web pages, but also extended to emails, files and other supported data types. The annotation tool-module described in this paper provides users with an ontology-based way of producing relationship metadata by either creating new instances or by specifying relationships amongst existing instances. This metadata creation process is facilitated by an ontology-supported navigation and the support of inference mechanisms on already existing metadata.